From Initiation To Development: Key Factors Shaping Digital Transformation In Local Government - Wessiani, Naning Aranti; Djunaedi, Achmad; Subarsono , Agustinus (Asian Journal of Social and Humanities, 2025)
The implementation of digital transformation in the public sector has become increasingly essential, particularly in developing countries where governance challenges and citizen expectations are rapidly evolving. While existing studies have identified various success factors for digital transformation—such as leadership, technological infrastructure, and organizational readiness—most of these works treat transformation as a linear process, without differentiating between its distinct stages. Furthermore, current research is predominantly situated in national-level or developed country contexts, offering limited insight into how local governments in resource-constrained environments initiate and sustain transformation efforts.This study aims to address these gaps by identifying the key factors that influence both the initiation and development stages of digital transformation within local governments in a developing country setting. Using a qualitative case study approach, two departments within the local government of Surabaya in Indonesia, were examined. The findings reveal two distinct categories of influential factors: those that trigger the initial adoption and those that accelerate the transformation process. This staged perspective provides practical insights for policymakers and public managers in similar contexts, emphasizing the need for tailored strategies that align with each phase of the transformation journey.